Serious Game for the Nursing Assessment of Home-Dwelling Older Adults: Development and Validation Study - Erica Busca; Silvia Caristia; Sara Palmira Bidone; Alessia Bolamperti; Sara Campagna; Arianna Cattaneo; Rosaria Lea; Doriana Montani; Antonio Scalogna; Erika Bassi; Alberto Dal Molin (JMIR Publications, 2024)
BackgroundThe use of serious games (SGs) in nursing education is increasing, with the COVID-19 pandemic significantly accelerating their development. A key feature of SGs is their flexibility, allowing students to train at any place and time as needed. Recently, there has been a shift from developing disease-specific SGs to games focused on broader health issues. However, there has been a lack of proposals to enhance nursing interventions in home and frail care settings. The REACtion project developed a SG to improve students' understanding and clinical reasoning in caring for home-dwelling older adults. ObjectiveThis study aims to describe the development of "REACtion Game" (RG) and explore its validity as an educational tool. A multidisciplinary team created a SG that simulates the assessment process of older adults in home settings by nurses. It features web-based scenarios, clickable objects, and a menu with tools, and medical records to enhance nursing students' knowledge and clinical reasoning skills. MethodsA prospective, observational study was conducted using the Dutch Society for Simulation in Healthcare's framework to validate the game. Further, 5 experts in home health care nursing evaluated content validity, while 30 students assessed construct validity, face validity, concurrent validity (by comparing game scores with those from the Nursing Clinical Reasoning Scale), game quality, and usability. Data were collected through self-administered web-based questionnaires and the debriefings of each match played. The students were enrolled in 2 postgraduate nursing programs: a master of science in nursing degree and a first-level continuing education in family and community nursing. ResultsExperts rated the content validity highly after revisions (universal agreement calculation method of scale-level content validity index=0.97). The sample consisted of 30 students, predominantly women (n=20, 67%) and aged younger than 45 years (n=23, 77%) with no prior experience in SG. Almost all students had a positive impression of RG as an attractive and useful method for learning new knowledge. Participants found the cases, scenarios, and dialogues realistic (face validity) and of high quality, though usability aspects such as instructions clarity and intelligibility of game progression were less favored. Construct validity showed general agreement on the game's educational value, with family and community nursing students reporting more consistent alignment with educational goals. Overall, RG scores correlated positively with time spent playing but showed limited correlation with Nursing Clinical Reasoning Scale scores. ConclusionsThis study developed and validated a nursing education game, especially valuable as simulation is underused in some curricula. Created during the pandemic, it offered a digital learning environment. Although the game shows potential, further testing is needed for usability, concurrent validity, and functional improvements. Future research should involve larger samples to fully validate the game and assess its impact on academic achievement.